Myosteatosis and bone marrow adiposity are not associated among postmenopausal women with fragility fractures - Badr, Sammy; Dapvril, Héloïse; Lombardo, Daniela; Khizindar, Huda; Martin, Claire; Cortet, Bernard; Cotten, Anne; Paccou, Julien (Frontiers in Endocrinology, 2023)
Objectives: Although paravertebral intramuscular fatty infiltration (known as myosteatosis) following a vertebral fracture is well-known, scarce data are available regarding interactions between muscle, bone, and other fat depots. Based on a homogeneous cohort comprising postmenopausal women with or without a history of fragility fracture, we aimed to better depict the interrelationship between myosteatosis and bone marrow adiposity (BMA). Methods: 102 postmenopausal women were included, 56 of whom had a fragility fracture. Mean proton density fat fraction (PDFF) was measured in the psoas (PDFFPsoas) and paravertebral (PDFFParavertebral) muscles at the lumbar level, as well as in the lumbar spine and non-dominant hip using chemical shift encoding-based water-fat imaging. Visceral adipose tissue (VAT) and total body fat (TBF) were assessed using dual X-ray absorptiometry. Statistical models were adjusted for age, weight, height (all comparisons), and bone mineral density (when considering BMA). Results: PDFF in the psoas and paravertebral muscles was higher in the fracture group compared to controls, even after adjustment for age, weight, and height (PDFFPsoas = 17.1 ± 6.1% versus 13.5 ± 4.9%, p=0.004; PDFFParavertebral = 34.4 ± 13.6% versus 24.9 ± 8.8%, p=0.002). Higher PDFFParavertebral was associated with lower PDFF at the lumbar spine (β = -6.80 ± 2.85, p=0.022) among controls but not in the fracture group. In both groups, a significant relationship between higher PDFFPsoas and higher VAT was observed (β = 20.27 ± 9.62, p=0.040 in the fracture group, and β = 37.49 ± 8.65, p<0.001 in the control group). Although solely observed among controls, a similar relationship was observed between PDFFParavertebral and TBF (β = 6.57 ± 1.80, p<0.001). No significant association was observed between BMA and other fat depots. Conclusion: Myosteatosis is not associated with BMA among postmenopausal women with fragility fractures. Whereas myosteatosis was associated with other fat depots, BMA appears uniquely regulated.